The use of mural painting and graffiti art as urban landscape in modern times / Norlida Daud ... [et al.] - Daud, Norlida; Ibrahim, Noor Aileen; Mohamad, Sarman; Taharuddin, Nurul Shima; Ahmad, Nani Hartina (2023)
Public art encompasses the feeling of artist or community, it can be found in plenty of form, techniques and processes. It can be either temporary or permanently installed in public areas (Chang, 2008). Few example of public arts are sculptures, archway, monuments, street furniture and artwork installed or painted on wall, mural also can be categorized as public art and become more popular nowadays. In recent years, murals have gained widespread acceptance and are increasingly employed as a means of conveying messages and enhancing the aesthetic appeal of urban landscapes. This emerging trend resonates with the community's aspiration for an improved quality environment, driven by the growing urban population in Malaysia and the need for enhanced urban landscapes (Mohd Fabian, 2010). Furthermore, murals make significant contributions to the tourism sector by captivating people's attention with their painted landscapes. It is worth noting that public art, including murals, now holds considerable commercial potential and is no longer commonly associated with vandalism.